The right look: Conservative politicians look better and their voters reward it - Niclas Berggren; Henrik Jordahl; Panu Poutvaara (Institute for the Study of Labor (IZA), 2011)
Previous research has established that good-looking political candidates win more votes. We extend this line of research by examining differences between parties on the left and on the right of the political spectrum. Our study combines data on personal votes in real elections with a web survey in which 2,513 non-Finnish respondents evaluated the facial appearance of 1,357 Finnish political candidates. We find that political candidates on the right are better looking in both municipal and parliamentary elections and that they have a larger beauty premium in municipal, but not in parliamentary, elections. As municipal candidates are relatively unknown, the beauty-premium gap indicates that voters especially those to the right use beauty as a cue for candidate ideology or quality in the municipal elections.
urn:nbn:de:101:1-201104113865
Keywords: D72; J45; J70; 330; beauty; elections; political candidates; appearance; ideology; parties; Wahlkampf; Politiker; Wahlverhalten; Ideologie; Public Choice; Finnland